Enhancement in grain-structure and mechanical properties of laser reversion treated metastable austenitic stainless steel. (15th March 2016) - Hamada, A.S.; Järvenpää, A.; Ahmed, E.; Sahu, P.; Farahat, A.I.Z.
Abstract: In this study, the effect of laser reversion annealing on grain refinement and enhancement of the mechanical properties in a cold deformed 301LN stainless steel is reported. The steel sheets were pre-strained to 60% reduction (0.9 true strain) by cold rolling, which promotes deformation-induced austenite-to-martensite transformation, attributable to the low stacking fault energy of the concerned steel. Ytterbium-doped:yttrium aluminum garnet (Yb:YAG) laser was selected as a heat source to prompt laser reversion annealing. The surface temperature measured during laser processing was correlated to the laser scan rate. The laser treated specimens were subjected to microhardness measurements and uniaxial tension tests. The corresponding microstructures were investigated by a scanning laser microscope and scanning electron microscope equipped with electron backscattered diffraction (EBSD). The laser scan rate significantly affected the grain refinement, the microhardness values as well as the tensile properties of the cold deformed 301LN stainless steel. With decreasing the laser scan rate from 10.5 to 7.5 mm/s, the homogeneity of the grain structure was markedly enhanced. Graphical abstract: Highlights: Laser reversion annealing of a cold deformed 301LN stainless steel was investigated. The corresponding microstructures were studied by laser microscope and SEM equipped with EBSD. Laser scan rate notably affected the grain refinement, microhardness, and tensile properties. Grain structure homogeneity was clearly enhanced by decreasing laser speed from 10.5 to 7.5 mm/s.